Mental Health and Indian Youth - Dr. Kashi Nath Pandey (International Journal of Indian Psychȯlogy, 2025)
Mental health issues among youth are a global concern, with considerable implications for individuals and society. This research paper critically examines the state of mental health among Indian youth, exploring the prevalence, risk factors, and implications of mental health disorders. It also discusses existing support systems, intervention programs, and future recommendations for addressing mental health challenges. By synthesizing existing literature, this study aims to provide a comprehensive understanding of mental health in the context of India’s youth, highlighting the urgent need for focused research and policy intervention.